Silver nanoparticles coated by green graphene quantum dots for accelerating the healing of MRSA-infected wounds. (21st October 2020) - Zhong, Xianghua; Tong, Chunyi; Liu, Tiansheng; Li, Li; Liu, Xu; Yang, Yuejun; Liu, Rushi; Liu, Bin
Abstract : Bacterial infection, especially multidrug-resistant bacteria-induced infection, threatens human health seriously, which has posed great challenges for clinical therapy. Abstract : Bacterial infection, especially multidrug-resistant bacteria-induced infection, threatens human health seriously, which has posed great challenges for clinical therapy. The overuse of conventional antibiotics has given rise to bacterial resistance that severely restricts the clinical treatment options of conventional antibiotics. The development of highly effective antibacterial materials and therapeutic strategies to inhibit the multidrug-resistant bacteria-induced infections is of great urgency. Although silver nanoparticles (AgNPs) have exhibited certain effectiveness in killing multidrug-resistant bacteria, their antibacterial efficacy and biosafety are still unsatisfactory. In this work, we prepared graphene quantum dots (GQDs) by a green synthesis method with the natural polymer starch as a precursor for uniformly decorating AgNPs to form GQDs coated AgNPs (GQDs@Ag). The nanocomplex was comprehensively characterized, and its antibacterial activity and biosafety were systematically investigated. The characterization results revealed that the successfully constructed GQDs@Ag hybrids with improved dispersion and stability are composed of AgNPs closely and uniformly surrounded by the GQDs. Furthermore, in vitro and in vivo results demonstrated that GQDs@Ag hybrids with superior biosafety showed a markedly enhanced effect in killing MRSA and accelerating MRSA -infected wound healing as compared to AgNPs alone. Collectively, these results suggest that the biocompatible nanosystem of GQDs@Ag exhibits great potential in clinical application for MRSA infection.